Loyalty rules! : how today's leaders build lasting relationships - Reichheld, Frederick F. (Boston : Harvard Business School Press, 2001)
In this provocative yet practical book, Fred Reichheld argues that loyalty provides the acid test for leadership in today's volatile business environment, and that most leaders deserve failing grades. In fact, the author is quick to highlight that less than half of today's employees believe their company deserves their loyalty. Reichheld's 1996 international bestseller, The Loyalty Effect, set out his theory and convincingly established the link between loyalty and bottom-line profits. In Loyalty Rules!, he moves from theory to practice, using vivid stories from many of today's most successful companies to illustrate how superior leaders create networks of mutually beneficial, trust-inspiring partnerships between customers, employees, suppliers, and investors. Reichheld's research demonstrates that effective leaders build relationships upon six bedrock principles of loyalty: Play to win/win: profiting at the expense of partners is a short cut to a dead end; Be picky: membership is a privilege; Keep it simple: complexity is the enemy of speed and flexibility; Reward the right results: worthy partners deserve worthy goals; Listen hard and talk straight: long-term relationships require honest, two-way communication and learning; and Preach what you practice: actions often speak louder than words but together, they are unbeatable.
Includes bibliographical references and index.
Keywords: Customer loyalty; Customer relations; Employee loyalty; Leadership